Effectiveness of myofascial release technique versus dry cupping therapy in management of patients with non-specific low back pain - Mohamed, Rabab A; Abdallah, Ghada A; Hafez, Hanaa Ali; Helmy, Amany Mahmoud; Nassif, Ayman A; Fergany, Lamyaa Ahmed; Toson, Rokaia A; Mousa Ghaleb, Heba Ahmed; Atta, Hanaa K (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to compare the effects of myofascial release and cupping techniques on pain levels, spinal mobility, and functional impairments in individuals with non-specific low back pain (NSLBP). This study was a randomized controlled trial employing a pre-test and post-test design. Sixty male and female patients diagnosed with NSLBP, aged 45 to 55, participated. They were randomly assigned to three groups: Group A, in which 20 patients received myofascial release (MFR) along with conventional physical therapy; Group B, in which 20 patients received cupping therapy in addition to conventional physical therapy; and Group C, in which 20 patients received only conventional physical therapy. All groups underwent treatment three times per week for four consecutive weeks. Visual analog scale (VAS) results indicated significant improvements within each group; however, group A demonstrated superior pain reduction compared to groups B and C (p<0.05). Additionally, all three groups exhibited improvements in functional disability levels and range of motion, with group A showing statistically significant superiority over the other two groups (p<0.05). In conclusion, myofascial release therapy was more effective than cupping therapy in reducing pain, improving functional impairment, and enhancing lumbar range of motion in NSLBP patients.